Position statement on use of antivenom - Amin, Md Robed; Sayeed, Abdullah Abu; Alam, Rabiul; Ghose, Aniruddha; Shahjahan, Mohammed; Mahbubur Rahman, Abu Shahin Mohammed; Mondal, Ratindra Nath; Faiz, Mohammad Abul (Bangladesh Journal of Medicine, 2022)
Abstract not available Bangladesh J Medicine 2022; 33: 317